AB1146 The Relationship Between Function and the Periarticular Knee Structure Measured by Ultrasound in Obese Patients with Knee Osteoarthritis on a Waiting List for Total Knee Replacement. (9th June 2015) - Nuñez, M.; Sastre, S.; Nuñez, E.; Montañana, J.; Segura, V.; Lozano, L.; Segur, J.M.; Alemany, X.; Moreno, J.
Abstract : Background: An increasing number of obese patients are candidates for total knee replacement (TKR). However, objective criteria for decision making in these patients are lacking. We hypothesized that quantification of the periarticular knee structure in elderly obese patients on a waiting list for TKR could provide additional information/indicators for decision-making. Objectives: To evaluate the influence of the anthropometric properties and periarticular structures of the knee as assessed by ultrasound imaging on functional capacity in obese patients with knee osteoarthritis on a waiting list for TKR. Methods: Cross-sectional observational study. Sociodemographic and anthropometric variables, body mass index (BMI), comorbidities and physical activity (regular physical exercise ≥3 times per week for ≥30 minutes per session and remaining seated ≤6 hours per day) were collected. Function was measured using the Timed Up and Go (TUG) test (functional mobility and balance) (categorized as 13.5/>13.5 seconds). Periarticular knee structures were evaluated using ultrasound (subcutaneous fat thickness [distance from the skin to the fascia, in mm], quadriceps/rectus femoris thickness [distance between the fascia and the femur, in mm]). Statistical analysis: Multivariate logistic regression model was used to discover the combination of variables which best explained function. The goodness of fit of the classification of the predictive model was assessed using a receiver operating characteristic (ROC) curve. Results: 54 patients, (41 female, mean age 69.9 years (SD 7), mean BMI 35.7 (SD 4), 58% with >2 comorbidities, 51.9% physically active) were studied. Mean TUG was 15.5 seconds (SD 8) (50% TUG >13.5 seconds). Mean subcutaneous fat thickness was 25.1 mm (SD 11), and mean quadriceps/rectus femoris thickness was 37.4 mm. (SD 9). Multivariable analysis identified age >75 years (OR 11.10 [11.4–86.9] p=0.024), and subcutaneous fat thickness (OR 1.09 [1.09–1.2] p=0.013) as predictors of worse TUG scores. The area under the ROC curve was 0.71. Conclusions: Periarticular fat, but not the BMI, was an independent predictor of a greater reduction in functional mobility in these patients. This suggest that exercises to maintain and improve function could improve the functional status of patients on a waiting list, and delay TKR. Ultrasound is useful to determine objective measures of function in these patients. References: Villareal DT, et al. Physical frailty and body composition in obese elderly men and women. Obesity Res 2004;12 (6):913-20. Núñez M, et al. Good quality of life in severely obese total knee replacement patients: a case-control study.Obes Surg. 2011 Aug;21(8):1203-8. Katz JN. Appropriateness of Total Knee Arthroplasty. Editorial Arthritis Rheumatol 2014;66(8): 1979–1981.doi: 10.1002/art.38688. Acknowledgements: This work has been funded by the project PI13/00948, integrated in the Plan Nacional I+D+I and co-funded by ISCIII-Subdirecciόn General de Evaluaciόn and European Regional Development Fund (ERDF). Disclosure of Interest: None declared